Information Analysis of the dissemination of the plastic arts in the galleries of Tabasco: El Jaguar Despertado Art Gallery: A place full of history and art - Pérez Montero, Donovan Javier (Cinzontle, 2024)
The objective of this study is to analyze the function that art galleries have in the dissemination of the plastic arts in the state of Tabasco, for this the study was used case from the gallery The Awakened Jaguar. The methodology used was documentary research, as well as non-participant observation, taking as unit of analysis the information collected in various documents and the work of field made. Among the findings, it stands out that this gallery as an instance governmental public does exercise the function of being an accessible space for Tabasco artists who seek to promote themselves and actively participate in the art market as a means of employment. They have a very reduced because they are only limited to institutional virtual networks, which prevents the reach is massive and they can become art-consuming public. HE suggests that they diversify their promotion mechanisms and create other activities that incite the interest and assistance of society.